Dietary supplementation of Chinese herbal medicines enhances the immune response and resistance of rainbow trout (Oncorhynchus mykiss) to infectious hematopoietic necrosis virus - Wang, Qi; Pan, Yucai; Huang, Jinqiang; Li, Yongjuan; Wu, Shenji; Zhao, Lu; Sun, Tongzhen; Kang, Yujun; Liu, Zhe (Frontiers in Veterinary Science, 2024)
Rainbow trout is widely farmed economical cold-water fish worldwide, but the prevalence of infectious hematopoietic necrosis virus (IHNV) presents a severe risk to the sector, resulting in high mortality and huge economic losses. In this study, the impacts of different concentrations (0, 10, 20, 30 g/kg) of Chinese herbal medicines mixture (CHMM) on immune response, and resistance of rainbow trout to IHNV infection were evaluated. The results shown that CHMM were noticeably increased (P < 0.05) T-SOD, CAT, AST, ALT, ACP and AKP activities, and decreased MDA content.The NF-κB, TNF-α, IFN-β, IL-1β, JAK1, HSP70 and HSP90 expression were significantly up-regulated (P < 0.05) in all CHMM, while SOCS2 expression was downregulated (P < 0.05). Following infection with IHNV, feeding rainbow trout with varying amounts of CHMM resulted in noticeably increased (P < 0.05) T-SOD, ACP, and AKP activities, and significantly decreased (P < 0.05) MDA content and AST and ALT activities. The TNF-α、IFN-β、IL-1β、HSP70 and HSP90 expression were significantly up-regulated (P < 0.05) in all CHMM, while JAK1 and SOCS2 expression were down-regulated. The IHNV G protein gene expression level at a dosage of 20 g/kg was notably lower compared to the other CHMM feeding groups. This study gives solid scientific basis for promoting CHMM as immunostimulants to boost the antiviral immunity in rainbow trout.